CRITICAL ANALYSIS OF BIBLIOGRAPHIC SOURCES WITHIN HISTORY OF ART DISCIPLINE - RAŞCHITOR TATIANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2020)
In the scientific and didactic activity carried out within the art history module there occur some problems with documentation and information processing. Solving these issues is not only the prerogative of the teacher, but also of the student. In the learning process, the student should continuously develop the ability to find, select and analyze information. The article outlines the main problems encountered in the process of documentation in the art history module and the methods of clarifying them; the author classified and presented the information and bibliographic sources specific to the discipline, but also the techniques of developing critical thinking skills applicable to the described context. She has elaborated 3 learning activities, in which 4 documentation problems have been analyzed.